Electrochemical device

By using reversible doped porous carbon material positive and lithium ion negative active substances in electrochemical devices, combined with electrolytic solution of lithium salt and specific carbonate solvents, the problem of decreased electrochemical device performance is solved. Internal resistance stability and reliability improvement.

CN119343731APending Publication Date: 2025-01-21PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380045843.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-29
Filing Date
2023-07-28
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

It is necessary to suppress the performance of the electrochemical device.

Method used

Using a porous carbon material positive electrode containing reversibly doped anions and a negative active material reversibly doped with lithium ions, an electrolyte is combined with an imide-based lithium salt and a specific proportion of cyclic and chain carbonate solvents to ensure the total surface functional group density In the range of 0.01~0.2.

Benefits of technology

Effectively suppress the reduction of the performance of electrochemical devices, reduce the increase in internal resistance, and improve the reliability of electrochemical devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119343731A_ABST
    Figure CN119343731A_ABST
Patent Text Reader

Abstract

An electrochemical device is provided with: a positive electrode containing a positive electrode active material reversibly doped with anions; a negative electrode containing a negative electrode active material reversibly doped with lithium ions; and an electrolyte solution containing a solvent and a lithium salt. The lithium salt contains an imide-based lithium salt, and the positive electrode active material contains a porous carbon material. The total surface functional group amount F (meq / g) per unit weight of the porous carbon material and the area S (nm2) of a circle having the average pore diameter of the porous carbon material as the diameter satisfy the relationship 0.01 < = F / S < = 0.20.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to electrochemical devices. Background Art

[0002] In recent years, electrochemical devices that combine the power storage principle of lithium-ion secondary batteries and double-layer capacitors have attracted attention. Such electrochemical devices usually use a polarizable electrode for the positive electrode and a non-polarizable electrode for the negative electrode. As a result, it is expected that electrochemical devices that have both the high energy density of lithium-ion secondary batteries and the high output characteristics of double-layer capacitors will be obtained.

[0003] Patent document 1 proposes a lithium ion capacitor having an electrolyte, which comprises: an electrolyte which is a mixture of LiFSI and LiBF4 and in which the molar ratio of LiFSI to LiBF4 is 90 / 10 to 30 / 70, a solvent comprising at least one of cyclic or chain carbonate compounds, and a film forming agent, wherein the concentration of the electrolyte in the electrolyte is 1.2 to 1.8 mol / L.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2017-216310 Summary of the invention

[0007] Problems to be solved by the invention

[0008] It is necessary to suppress the performance degradation of electrochemical devices.

[0009] Means used to solve problems

[0010] One aspect of the present disclosure relates to an electrochemical device comprising: a positive electrode comprising a positive electrode active material reversibly doped with anions, a negative electrode comprising a negative electrode active material reversibly doped with lithium ions, and an electrolyte comprising a solvent and a lithium salt, wherein the lithium salt comprises an imide-based lithium salt, the positive electrode active material comprises a porous carbon material, and a ratio of a total surface functional group amount per unit mass F (meq / g) of the porous carbon material to an area S (nm) of a circle having an average pore diameter of the porous carbon material as a diameter 2 ) satisfies the relationship 0.01≤F / S≤0.20.

[0011] Effects of the Invention

[0012] According to the present disclosure, it is possible to suppress degradation in the performance of an electrochemical device.

[0013] The novel features of the present invention are described in the appended claims, but the present invention relates to both the structure and the content, and together with other objects and features of the present invention, will be further fully understood through the following detailed description with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 is a diagram schematically showing a part of the cross section of a porous carbon material.

[0015] Figure 2 This is a longitudinal sectional view showing an example of an electrochemical device. DETAILED DESCRIPTION

[0016] Hereinafter, the embodiments of the present disclosure will be described with examples, but the present disclosure is not limited to the examples described below. The following description sometimes illustrates specific numerical values ​​and materials, but other numerical values ​​and materials can be applied as long as the effects of the present disclosure can be obtained. In this specification, the description of "numerical value A to numerical value B" includes numerical value A and numerical value B, which can be replaced by "numerical value A or above and numerical value B or below". In the following description, when the lower limit and upper limit are illustrated for numerical values ​​of specific physical properties, conditions, etc., as long as the lower limit does not reach above the upper limit, any of the illustrated lower limits can be arbitrarily combined with any of the illustrated upper limits. When multiple materials are illustrated, one of them can be selected and used alone, or two or more can be used in combination.

[0017] In addition, the present disclosure includes a combination of matters recorded in two or more claims arbitrarily selected from the plurality of claims recorded in the appendix. That is, as long as no technical contradiction occurs, matters recorded in two or more claims arbitrarily selected from the plurality of claims recorded in the appendix may be combined.

[0018] The electrochemical device of the embodiment of the present disclosure comprises: a positive electrode including a positive electrode active material reversibly doped with anions, a negative electrode including a negative electrode active material reversibly doped with lithium ions, and an electrolyte. The electrolyte has lithium ion conductivity and includes a lithium salt and a solvent. In the electrolyte, the lithium salt can form lithium ions and anions by dissolving in the solvent.

[0019] In the positive electrode, anions are doped into the positive electrode active material during charging, and the anions are dedoped from the positive electrode active material during discharge. When anions are adsorbed to the positive electrode active material in the electrolyte, a double electric layer is formed, which exhibits capacity. When anions are desorbed from the positive electrode active material, a non-Faraday current flows. The positive electrode is an electrode that utilizes this phenomenon.

[0020] In the negative electrode, lithium ions are doped into the negative electrode active material during charging, and the lithium ions are dedoped from the negative electrode active material during discharge. The negative electrode undergoes a Faraday reaction of reversibly storing and releasing lithium ions, which exhibits capacity. The doping of lithium ions into the negative electrode active material refers to at least the phenomenon of storing lithium ions into the negative electrode active material, and is a concept that can also include the adsorption of lithium ions into the negative electrode active material, the chemical interaction between the negative electrode active material and lithium ions, etc.

[0021] The lithium salt of the electrolyte solution includes an imide-based lithium salt. The positive electrode active material includes a porous carbon material (e.g., activated carbon). The total surface functional group amount F (meq / g) per unit mass of the porous carbon material is related to the area S (nm) of a circle with an average pore diameter (hereinafter also referred to as "average pore diameter d") of the porous carbon material as its diameter. 2 ) satisfies the relationship 0.01≤F / S≤0.20.

[0022] The area S of a circle with the average pore diameter d as its diameter is calculated by π×(d / 2) 2 The formula is calculated.

[0023] Below, F / S (meq / g / nm 2 ) is also called "the total surface functional group density D of the average cross section of the pores" or simply "the total surface functional group density D". "The average cross section of the pores" refers to the cross section of the pores in which the area surrounded by the outline of the inner wall surface of the pores in the cross section of the porous carbon material is the same as the area of ​​the circle with the average pore diameter d as the diameter. "Total surface functional group density D" is an indicator of the functional group density in the pores of the porous carbon material.

[0024] Porous carbon materials usually have hydrophilic acidic functional groups (such as carboxyl, hydroxyl, quinone, phenolic hydroxyl, etc.) on the surface (inner wall of pores). Such porous carbon materials have the adsorption of solvated ions containing anions derived from lithium salts. Thus, a positive electrode with large capacity and low resistance can be obtained.

[0025] However, during charging, if the solvated ions of anions derived from lithium salts in the electrolyte move within the pores of the porous carbon material and adsorb on the inner wall of the pores, they react with the hydrophilic acidic functional groups present on the inner wall of the pores to generate acids such as HF, which attack the solvent, etc., and sometimes produce gas.

[0026] Here, Figure 1 is a diagram schematically showing a part of the cross section of a porous carbon material.

[0027] Figure 1The pores 2 of the porous carbon material 1 shown represent pores with an average cross section. The average cross section is, for example, a cross section of the porous carbon material 1 perpendicular to the direction in which the pores extend. In this cross section, it is assumed that the contour of the inner wall surface 3 of the pore 2 is circular. That is, the diameter of the pore 2 is the average pore diameter d. There are acidic functional groups 4 on the inner wall surface 3 of the pore 2. The electrolyte 5 enters the pore 2. The electrolyte 5 contains a solvent 6, anions 7 and lithium ions (not shown). The anions 7 can combine with the solvent 6 to form solvated ions. During charging, the anions 7 can be adsorbed on the inner wall surface 3 of the pore 2. The total surface functional group density D varies depending on the amount of acidic functional groups 4 present on the inner wall surface 3 of the pore 2 and the size of the pore 2 (average pore diameter d). Factors that affect the above-mentioned side reaction (gas generation) include not only the amount of the acidic functional group 4, but also the size and stability of the anion 7, the size of the pore 2, and the distance L between the anion 7 and the acidic functional group 4 (inner wall surface 3) in the pore 2. The distance L affects the size of the anion 7 and the pore 2.

[0028] Therefore, the present inventors conducted intensive studies focusing on the types of anions and the total surface functional group density D. As a result, they obtained the following new findings (i) and (ii).

[0029] (i) When the lithium salt contained in the electrolyte is LiPF6, a side reaction (generation of HF gas) is likely to occur regardless of the total surface functional group density D. This is presumably because the solvated PF6 - The diameter is small and it is easy to move in the pores.

[0030] (ii) On the other hand, when the lithium salt contained in the electrolyte is an imide-based lithium salt (e.g., LiFSI), the degree of the side reaction (gas generation amount) changes according to the total surface functional group density D. It is speculated that this phenomenon, which is unique to the case of imide-based lithium salts, is due to the solvated imide-based anion (e.g., FSI anion) and the solvated PF6 - Compared with the larger diameter, it is not easy to enter the pores, so it is not easy to decompose.

[0031] Based on the above understanding, the inventors conducted further research. As a result, it was newly discovered that by making the total surface functional group density D within the range of 0.01 to 0.2 when using imide-based lithium salts, the above-mentioned side reactions and the performance degradation of the electrochemical device caused by them can be suppressed while ensuring the good solvated ion adsorption of the porous carbon material. It should be noted that the performance degradation of the electrochemical device includes, for example, an increase in DCR (internal resistance) accompanied by floating charge and a decrease in capacity.

[0032] When F / S is greater than 0.2, the density of the acidic functional groups in the pores of the porous carbon material increases, the above-mentioned side reaction proceeds, and the DCR increases during float charge.

[0033] When F / S is less than 0.01, the density of the acidic functional groups in the pores of the porous carbon material decreases, the solvated ion adsorbability of the porous carbon material decreases, and the DCR increases during float charge.

[0034] (Determination of total surface functional group amount F)

[0035] The total surface functional group amount F (meq / g) per unit mass of the porous carbon material can be determined by the following method.

[0036] The sample of the porous carbon material is dried in a dryer at 115°C ± 5°C for more than 3 hours, and then naturally cooled in the dryer for more than 20 minutes. 2g ± 0.01g of the sample is added to a stoppered conical flask (volume 100ml), and then 50ml of C2H5ONa solution (concentration 0.1mol / L) is added as a reagent. It should be noted that the sample is measured to the order of 0.1mg. The inputs (sample and reagent) in the conical flask are stirred for 2 hours, and then allowed to stand for 24 hours. After standing, stir again for 30 minutes. It should be noted that the stirring is carried out using a stirrer. Then, the stirred product is filtered using filter paper (5 kinds of C) to obtain a filtrate. For 25ml of the filtrate, titration is performed using an aqueous solution of HCl (concentration 0.1mol / L). The titration is performed using an automatic titrator while stirring the filtrate with a stirrer. The titration is terminated when the pH of the filtrate reaches 4.0, and the total titration amount t1 from the start to the end of the titration is measured. In addition, without adding a sample, the same amount of the reagent (C2H5ONa solution) was titrated in the same manner, and the total titration amount t2 until the pH reached 4.0 was measured (blank test).

[0037] The total surface functional group amount F (meq / g) was calculated by the following formula (1) using the obtained t1 (ml) and t2 (ml).

[0038] F=0.1×(t2-t1) (1)

[0039] (Measurement of average pore diameter d)

[0040] The average pore diameter d can be obtained by the following method.

[0041] Take 0.20g to 0.25g of a sample of porous carbon material, place the sample in a measuring dish consisting of a glass tube for specific surface area measurement, and dry and degas the sample in the measuring dish. Drying and degassing are carried out at a pressure of 6.67Pa and a temperature of 250℃±5℃ for more than 1 hour. Then, the mass of the sample in the measuring dish is measured to the order of 0.1mg. Then, the nitrogen adsorption amount of the sample at a temperature of -196℃ is measured using a specific surface area measuring device. The measuring device uses, for example, the automatic specific surface area / pore distribution measuring device "TriStar II 3020" manufactured by Shimadzu Corporation. Based on the measurement results of the adsorption amount, the specific surface area A is calculated by the BET multi-point method in the range of partial pressure (relative pressure) 0.001 to 0.2. The pore volume V is calculated based on the total nitrogen adsorption amount of the sample when the partial pressure (relative pressure) reaches 0.93.

[0042] The specific surface area A (m 2 / g) and pore volume V (cm 3 / g), and the average pore diameter d (nm) was calculated by the following formula (2).

[0043] d=(4V / A)×10 3 (2)

[0044] In addition, the above-mentioned total surface functional group amount F and average pore diameter d can be measured by disassembling the electrochemical device, taking out the positive electrode, washing it with a solvent such as dimethyl carbonate, drying it, taking the positive electrode mixture layer from the positive electrode, and using it as a sample. The other components (binder, etc.) contained in the positive electrode mixture other than the porous carbon material are small, and the influence of other components on the measurement of the total surface functional group amount F and the average pore diameter d is small.

[0045] (Porous Carbon Materials)

[0046] The porous carbon material can be made, for example, by heat-treating the raw material to carbonize it and activating the obtained carbide to make it porous. As raw materials, for example, wood, coconut shells, pulp waste liquid, coal-based asphalt obtained by thermal decomposition of coal or its pyrolysis, petroleum-based asphalt obtained by thermal decomposition of heavy oil or its pyrolysis, phenolic resin, petroleum-based coke, coal-based coke, etc. can be listed. As activation treatment, for example, gas activation using gases such as water vapor and chemical reagent activation using alkalis such as potassium hydroxide can be listed.

[0047] The total surface functional group amount F and area S (average pore diameter d) can be adjusted by changing the raw materials, heat treatment temperature, activation temperature of gas activation, type of chemical reagent, and the like.

[0048] The total surface functional group amount F is, for example, 0.05 meq / g or more and 1 meq / g or less. The average pore diameter d is, for example, 1.5 nm or more and 6 nm or less.

[0049] The porous carbon material is usually in a granular form. The average particle size of the porous carbon material is not particularly limited and may be greater than 1 μm and less than 20 μm, or greater than 3 μm and less than 15 μm. It should be noted that in this specification, the average particle size refers to the particle size (median particle size) at which the volume cumulative value reaches 50% in the volume-based particle size distribution measured by the laser diffraction / scattering method.

[0050] The specific surface area A of the porous carbon material is, for example, 1200 to 2500 m 2 / g, can be 1350~2300m 2 / g range. When the specific surface area A is 1200m 2 / g or more (e.g. 1350m 2 / g or more), it is easy to achieve high capacity. 2 / g or less (e.g. 2300m 2 / g or less), the contact area with the electrolyte solution becomes small, and the electrolyte solution decomposition accompanying the side reaction can be suppressed. The specific surface area A can be calculated by the method described above.

[0051] The specific surface area and average particle size of the porous carbon material can be adjusted by subjecting the porous carbon material to a pulverization treatment and / or a classification treatment. The pulverization treatment can be performed using a ball mill, a jet mill, or the like.

[0052] (Imide lithium salt)

[0053] The lithium salt includes an imide-based lithium salt. An imide-based lithium salt is a salt composed of a lithium ion and an imide-based anion. Examples of the imide-based anion include an imide-based anion containing a sulfur atom and a fluorine atom (e.g., a fluorinated alkylsulfonyl imide anion, a fluorinated sulfonyl imide anion, etc.).

[0054] Examples of imide anions include N(SO2C m F 2m+1 )(SO2C n F 2n+1 ) - (m and n are each independently an integer greater than 0.) etc. m and n may be 0 to 3, respectively, and may be 0, 1 or 2. The imide anion may be N(SO2CF3)2 - 、N(SO2C2F5)2 - 、N(SO2F)2 - .

[0055] Sometimes N(SO2F)2 - FSI - , will be used as FSI -The salt of lithium bis(fluorosulfonyl)imide and lithium ion is represented by LiFSI.

[0056] Among them, the imide lithium salt preferably contains LiFSI. By using LiFSI, there is a tendency that the DCR change rate at low temperature is significantly reduced. It can be considered that LiFSI has the effect of inhibiting the degradation of the positive electrode active material and the negative electrode active material. It can be considered that FSI - The bond between fluorine and sulfur is strong and has excellent stability. - Compared with the case of HF, the generation of HF can be suppressed, which helps to smoothly charge and discharge without damaging the surface of the active material.

[0057] Hereinafter, each component of the electrochemical device will be described in detail.

[0058] (positive electrode)

[0059] The positive electrode active material contains at least a porous carbon material (e.g., activated carbon having an average particle size of 1 μm to 20 μm, a specific surface area A of 1200 to 2500 m 2 / g of porous carbon material), and may contain other materials other than the porous carbon material (e.g., conductive polymer). The ratio of the porous carbon material in the positive electrode active material may be 60% by mass or more, or 80% by mass or more, and ideally 95% by mass or more. The positive electrode active material may be entirely porous carbon material.

[0060] The positive electrode, for example, comprises a positive electrode mixture layer and a positive electrode current collector carrying the positive electrode mixture layer. The positive electrode mixture layer contains a positive electrode active material as an essential component, and may contain a conductive agent, a binder, a thickener, etc. as optional components. The content of the positive electrode active material in the positive electrode mixture layer may be 70% by mass or more, and ideally 90% by mass or more. The thickness of the positive electrode mixture layer relative to a single surface of the positive electrode current collector is, for example, 10 to 300 μm.

[0061] As the conductive agent, carbon black, carbon fiber, etc. can be listed. As carbon black, acetylene black, Ketjen black, etc. can be listed. As the binder, fluororesin, acrylic resin, rubber material, etc. can be listed. As the thickener, cellulose derivatives, etc. can be listed.

[0062] The positive electrode mixture layer is formed by, for example, mixing a positive electrode active material, a conductive agent, etc., together with a dispersion medium to prepare a positive electrode mixture slurry, applying the positive electrode mixture slurry to a positive electrode current collector, and then drying the mixture.

[0063] The positive electrode current collector may be a sheet-shaped metal material. The sheet-shaped metal material may be a metal foil, a porous metal, an etched metal, etc. As the metal material, aluminum, an aluminum alloy, nickel, titanium, etc. may be used.

[0064] (negative electrode)

[0065] The negative electrode potential (25°C) is based on the lithium standard (vs. Li / Li + ) is 0.2V or less. Lithium ions are pre-doped into the negative electrode mixture layer in advance in such a way that the negative electrode potential in the electrolyte is 0.2V or less relative to metallic lithium. As a result, the potential of the negative electrode is reduced, the potential difference (i.e., voltage) between the positive electrode and the negative electrode is increased, and the energy density of the electrochemical device is improved. The amount of pre-doped lithium can be set to, for example, about 50% to 95% of the maximum amount that the negative electrode mixture layer can absorb.

[0066] Examples of the negative electrode active material include hardly graphitizable carbon, easily graphitizable carbon (soft carbon), graphite (natural graphite, artificial graphite, etc.), lithium titanium oxide (spinel lithium titanium oxide, etc.), silicon oxide, silicon alloy, tin oxide, tin alloy, and the like.

[0067] Among them, the negative electrode active material preferably includes difficult graphitization carbon. Compared with graphite, difficult graphitization carbon has lower resistance and higher capacity. When difficult graphitization carbon is used, it is easy to obtain a negative electrode with small low-temperature DCR and small expansion and contraction accompanying charge and discharge. Compared with graphite, difficult graphitization carbon has better affinity with propylene carbonate and is easier to reduce DCR.

[0068] The interplanar spacing of the (002) plane of non-graphitizable carbon measured by X-ray diffraction (i.e., the interplanar spacing between carbon layers) d002 can be The theoretical capacity of the difficult graphitizable carbon is, for example, preferably 150 mAh / g or more. The difficult graphitizable carbon preferably accounts for 50% by mass or more of the negative electrode active material, further 80% by mass or more, and further 95% by mass or more. In addition, the difficult graphitizable carbon preferably accounts for 40% by mass or more of the negative electrode mixture layer, further 70% by mass or more, and further 90% by mass or more.

[0069] From the perspective of high filling of the negative electrode active material and easy suppression of side reactions with the electrolyte, the average particle size of the negative electrode active material (especially non-graphitizable carbon) can be 1 μm to 20 μm, or 2 μm to 15 μm.

[0070] The negative electrode includes, for example, a negative electrode mixture layer and a negative electrode current collector carrying the negative electrode mixture layer. The negative electrode mixture layer contains a negative electrode active material as an essential component and may contain a conductive agent, a binder, a thickener, etc. as optional components. The thickness of the negative electrode mixture layer relative to one side of the negative electrode current collector is, for example, 10 to 300 μm.

[0071] Examples of the conductive agent include carbon black, carbon fiber, etc. Examples of the binder include fluororesins, acrylic resins, rubber materials, etc. Examples of the thickener include cellulose derivatives, etc.

[0072] The negative electrode mixture layer is formed by, for example, mixing a negative electrode active material, a conductive agent, etc., with a dispersion medium to prepare a negative electrode mixture slurry, applying the negative electrode mixture slurry to a negative electrode current collector, and then drying the mixture.

[0073] The negative electrode current collector may be a sheet-shaped metal material. The sheet-shaped metal material may be a metal foil, a porous metal, an etched metal, etc. As the metal material, copper, a copper alloy, nickel, stainless steel, etc. may be used.

[0074] (Electrolyte)

[0075] The concentration of the lithium salt in the electrolyte is, for example, 0.5 mol / L or more and 5 mol / L or less. The lithium salt includes an imide-based lithium salt and may include other components other than the imide-based lithium salt. The ratio of the imide-based lithium salt in the lithium salt is preferably 50 mol% or more, may be 70 mol% or more, may be 90 mol% or more, or the lithium salt may be entirely imide-based lithium salt.

[0076] Examples of other components other than the imide lithium salt include LiClO4, LiBF4, LiPF6, LiAlCl4, LiSbF6, LiSCN, LiCF3SO3, LiFSO3, LiCF3CO2, LiAsF6, LiB 10 Cl 10 , LiCl, LiBr, LiI, LiBCl4, etc. These may be used alone or in combination of two or more.

[0077] As the solvent, cyclic carbonates such as ethylene carbonate, propylene carbonate, and butylene carbonate, chain carbonates such as dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate, aliphatic carboxylates such as methyl formate, methyl acetate, methyl propionate, and ethyl propionate, lactones such as γ-butyrolactone and γ-valerolactone, chain ethers such as 1,2-dimethoxyethane, 1,2-diethoxyethane, and ethoxymethoxyethane (EME), cyclic ethers such as tetrahydrofuran and 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, acetamide, dimethylformamide, dioxolane, acetonitrile, propionitrile, nitromethane, ethylene glycol diethyl ether (ethyl monoglyme), trimethoxymethane, sulfolane, methyl sulfolane, 1,3-propane sultone, etc. can be used alone or in combination of two or more.

[0078] From the viewpoint of suppressing the increase of DCR accompanying float charge, the volume ratio of cyclic carbonate to linear carbonate (for example, the volume ratio of propylene carbonate to ethyl methyl carbonate) is preferably 1 / 9 to 9 / 1, more preferably 2 / 8 to 8 / 2.

[0079] The cyclic carbonate preferably comprises propylene carbonate, preferably substantially does not contain ethylene carbonate. It should be noted that the above-mentioned "substantially does not contain" refers to being below the detection limit in the composition analysis of the electrolyte. As the composition analysis of the electrolyte, for example, gas chromatography-mass spectrometry (GC / MS), ion chromatography (IC), nuclear magnetic resonance spectroscopy (NMR) etc. can be used.

[0080] In the case of propylene carbonate, the melting point is lower than that of ethylene carbonate, and the electrolyte is less likely to solidify, so it is easy to obtain an electrolyte with a moderately low viscosity, and the ion conductivity at low temperature is excellent. In addition, propylene carbonate has a methyl group, and the steric hindrance is larger than that of ethylene carbonate, so it is not easy to be decomposed by an acid such as HF, and it is easy to suppress the increase of DCR.

[0081] The ratio of propylene carbonate to the cyclic carbonate may be 30% by volume or more, 50% by volume or more, and may be 80% by volume at most.

[0082] The linear carbonate preferably contains ethyl methyl carbonate, and preferably contains substantially no dimethyl carbonate or diethyl carbonate. In this case, the ratio of ethyl methyl carbonate to the linear carbonate may be 60% by volume or more, or 80% by volume or more.

[0083] In the case of ethyl methyl carbonate, the melting point is lower than that of dimethyl carbonate, the solidification is more difficult at low temperature, and the viscosity is lower. In the case of ethyl methyl carbonate, the conductivity is higher and the viscosity is lower than that of diethyl carbonate. Ethyl methyl carbonate can further reduce the DCR at low temperature.

[0084] The electrolyte may contain various additives as required. For example, unsaturated carbonates such as vinylene carbonate, vinylethylene carbonate, and divinylethylene carbonate may be added as additives to form a low-resistance film on the negative electrode surface.

[0085] (Isolated Body)

[0086] It is desirable to arrange a separator between the positive electrode and the negative electrode. As the separator, a nonwoven fabric made of cellulose fiber, a nonwoven fabric made of glass fiber, a microporous film made of polyolefin, a woven fabric or a nonwoven fabric can be used. The thickness of the separator is, for example, 8 to 300 μm, preferably 8 to 40 μm.

[0087] Figure 22 is a longitudinal sectional view showing an example of an electrochemical device. The electrochemical device 200 comprises an electrode body 100, an electrolyte (not shown), a metal bottomed battery case 210 for accommodating the electrode body 100 and the electrolyte, and a sealing plate 220 for sealing the opening of the battery case 210. The electrode body 100 is a columnar winding body formed by winding a strip-shaped positive electrode 10 and a strip-shaped negative electrode 20 with a separator 30 sandwiched between the positive electrode 10 and the negative electrode 20. A gasket 221 is arranged at the peripheral portion of the sealing plate 220, and the interior of the battery case 210 is sealed by embedding the open end of the battery case 210 into the gasket 221. The positive electrode collector plate 13 having a through hole 13h in the center is welded to the exposed portion 11x of the positive electrode core material. The other end of the tab lead 15 connected to the positive electrode collector plate 13 at one end is connected to the inner surface of the sealing plate 220. Therefore, the sealing plate 220 has a function as an external positive terminal. On the other hand, the negative electrode collector plate 23 is welded to the negative electrode core material exposed portion 21x. The negative electrode collector plate 23 is directly welded to the welding member provided on the inner bottom surface of the battery case 210. Therefore, the battery case 210 has a function as an external negative terminal.

[0088] The positive electrode collector plate 13 is a roughly disc-shaped metal plate. A through hole constituting a passage for the electrolyte is preferably formed in the central portion of the positive electrode collector plate. The material of the positive electrode collector plate includes, for example, aluminum, aluminum alloy, titanium, stainless steel, etc. The material of the positive electrode collector plate can be the same as that of the positive electrode collector.

[0089] The negative electrode current collector plate 23 is a substantially disc-shaped metal plate. The negative electrode current collector plate may be made of, for example, copper, copper alloy, nickel, stainless steel, etc. The negative electrode current collector plate may be made of the same material as the negative electrode current collector.

[0090] Electrochemical devices are not limited to Figure 2 The wound electrochemical device shown in the figure may be a stacked electrochemical device. That is, the electrode body may be a stacked body in which a sheet-like positive electrode and a negative electrode are stacked with a separator sandwiched between the positive and negative electrodes.

[0091] Postscript

[0092] The following techniques are disclosed through the description of the above embodiments.

[0093] (Technology 1)

[0094] An electrochemical device comprising:

[0095] A positive electrode comprising a positive electrode active material reversibly doped with anions,

[0096] A negative electrode including a negative electrode active material reversibly doped with lithium ions, and

[0097] an electrolyte comprising a solvent and a lithium salt,

[0098] The lithium salt includes an imide lithium salt.

[0099] The positive electrode active material comprises a porous carbon material.

[0100] The total surface functional group amount per unit mass of the porous carbon material F (meq / g) and the area S (nm) of a circle with the average pore size of the porous carbon material as its diameter are 2 ) satisfies the relationship 0.01≤F / S≤0.2.

[0101] (Technique 2)

[0102] The electrochemical device according to technology 1, wherein the imide-based lithium salt includes lithium bis(fluorosulfonyl)imide.

[0103] (Technique 3)

[0104] The electrochemical device according to technology 1 or 2, wherein the solvent contains a cyclic carbonate and a chain carbonate.

[0105] (Technique 4)

[0106] The electrochemical device according to technology 3, wherein the volume ratio of the cyclic carbonate to the linear carbonate is 1 / 4 or more and 4 or less.

[0107] (Technique 5)

[0108] The electrochemical device according to technology 3 or 4, wherein the cyclic carbonate comprises propylene carbonate and substantially contains no ethylene carbonate.

[0109] (Technique 6)

[0110] The electrochemical device according to any one of techniques 3 to 5, wherein the chain carbonate comprises ethyl methyl carbonate and substantially contains no dimethyl carbonate or diethyl carbonate.

[0111] (Technique 7)

[0112] The electrochemical device according to any one of techniques 1 to 6, wherein the negative electrode active material contains hardly graphitizable carbon.

[0113] [Example]

[0114] Hereinafter, the present disclosure will be described in more detail based on examples, but the present disclosure is not limited to the examples.

[0115] 《Device A1~A14, Device B1~B18》

[0116] (Production of positive electrode)

[0117] 88 parts by mass of positive electrode active material, 2 parts by mass of polytetrafluoroethylene (PTFE), 4 parts by mass of carboxymethyl cellulose, and 6 parts by mass of acetylene black were dispersed in water to obtain a positive electrode mixture slurry. The positive electrode mixture slurry was applied to both sides of an aluminum foil (thickness 30 μm) as a positive electrode collector, and the coating was dried and rolled to form a positive electrode mixture layer to obtain a positive electrode.

[0118] As the positive electrode active material, porous carbon materials (activated carbon particles) a1 to a14 and b1 to b2 shown in Table 1 were used.

[0119] Table 1

[0120]

[0121] (Production of negative electrode)

[0122] 90 parts by mass of non-graphitizable carbon, 5 parts by mass of Ketjen black, 1.5 parts by mass of carboxymethyl cellulose, and 3 parts by mass of styrene-butadiene rubber were dispersed in water to obtain a negative electrode mixture slurry. The negative electrode mixture slurry was applied to both sides of a copper foil (thickness 8 μm) as a negative electrode collector to form a coating film, which was dried and rolled to form a negative electrode mixture layer to obtain a negative electrode.

[0123] Next, a metal lithium foil having an amount calculated so that the negative electrode potential in the electrolyte after completion of pre-doping becomes 0.2 V or less with respect to metal lithium is attached to the negative electrode mixture layer.

[0124] (Production of Electrode Body)

[0125] The positive electrode and the negative electrode were wound into a column with a separator (thickness 25 μm) of cellulose nonwoven fabric sandwiched between them to form an electrode body. At this time, the exposed portion of the positive electrode collector protruded from one end face of the electrode body, and the exposed portion of the negative electrode collector protruded from the other end face of the electrode body. Disc-shaped positive and negative collector plates were welded to the exposed portion of the positive and negative collectors, respectively.

[0126] (Preparation of Electrolyte)

[0127] The electrolyte is prepared by dissolving a lithium salt in a solvent. The solvent is a mixture of a cyclic carbonate and a chain carbonate in a volume ratio of 30:70. The cyclic carbonate and the chain carbonate are propylene carbonate (PC) and ethyl methyl carbonate (EMC), respectively. The lithium salt is LiFSI or LiPF6. The concentration of the lithium salt (LiFSI or LiPF6) in the electrolyte is set to 1.0 mol / L.

[0128] (Assembly of electrochemical device)

[0129] The electrode body is placed in a battery case with an opening and a bottom, and the tab lead connected to the positive electrode collector plate is connected to the inner surface of the sealing plate. Furthermore, the negative electrode collector plate is welded to the inner bottom surface of the battery case. After pouring the electrolyte into the battery case, the opening of the battery case is sealed with the sealing plate, and the battery case is assembled as shown in the figure. Figure 2 It should be noted that A1 to A14 in Table 2 are electrochemical devices of Examples. B1 to B2 in Table 2 and B3 to B18 in Table 3 are electrochemical devices of Comparative Examples.

[0130] Then, while applying a charging voltage of 3.8 V between the terminals of the positive electrode and the negative electrode, the battery was aged at 25° C. for 24 hours to pre-dope the negative electrode with lithium ions.

[0131] The following evaluations were performed on each electrochemical device.

[0132] [evaluate]

[0133] (Measurement of Initial Internal Resistance (DCR) of Electrochemical Device)

[0134] For the electrochemical device just after aging, at -30°C, the positive electrode area is 2 mA / cm 2 After constant current charging at a current density of 2000 volts until the voltage reaches 3.8 V, the voltage of 3.8 V is maintained for 10 minutes. Then, at -30°C, the positive electrode area is charged at 2 mA / cm 2 The battery was discharged at a constant current density until the voltage reached 2.2 V.

[0135] Using the discharge curve obtained by the above discharge (vertical axis: discharge voltage, horizontal axis: discharge time), find the first-order approximate straight line in the range from the start of discharge to 0.5 seconds to 2 seconds, and find the voltage VS of the intercept of the approximate straight line. Determine the value (V0-VS) of the voltage VS minus the voltage V0 at the start of discharge (0 seconds from the start of discharge) as ΔV. Use ΔV (V) and the current value during discharge (current density per unit positive electrode area 2mA / cm 2 × positive electrode area) Id, the internal resistance R1 (Ω) of the electrochemical device was calculated by the following formula (A).

[0136] Internal resistance R1=ΔV / Id(A)

[0137] (Measurement of internal resistance (DCR) of electrochemical device after floating charge test)

[0138] Next, a floating charge test was performed by applying a constant voltage of 3.8 V to the electrochemical device for 1000 hours in an environment of 85° C. Then, the internal resistance R2 (Ω) of the electrochemical device was obtained in the same manner as in R1.

[0139] Using the obtained R1 and R2, the DCR change rate (%) was calculated by the following formula (B).

[0140] DCR change rate = {(R2-R1) / R1}×100(B)

[0141] The smaller the DCR change rate, the more the internal resistance increase is suppressed, and the higher the reliability.

[0142] The evaluation results are shown in Tables 2 and 3.

[0143] Table 2

[0144]

[0145] Table 3

[0146]

[0147] Devices A1 to A14 have a smaller DCR change rate than devices B1 to B18, and the increase in internal resistance is further suppressed.

[0148] Installations A15-A26

[0149] In the preparation of the electrolyte, the content of the cyclic carbonate and the chain carbonate in the solvent is respectively made to be the value (volume %) shown in Table 4. The cyclic carbonate and the chain carbonate use the compounds shown in Table 4 respectively. It should be noted that in Table 4, EC is ethylene carbonate, DMC is dimethyl carbonate, and DEC is diethyl carbonate. In Table 4, in devices A22 to A26, cyclic carbonate (or chain carbonate according to the situation) uses two compounds, and the volume ratio of the two compounds is shown in brackets.

[0150] Except for the above, the same operation as that of the apparatus A8 was carried out to produce apparatuses A15 to A26, and the evaluation was performed. The evaluation results of apparatuses A15 to A26 are shown in Table 4 together with the apparatus A8.

[0151] Table 4

[0152]

[0153] In devices A15 to A26, as in device A8, the DCR change rate is reduced by using porous carbon material a8 as the positive electrode active material and LiFSI as the lithium salt of the electrolyte. In devices A8, A16 to A18 where the volume ratio of PC / EMC is 1 / 4 or more and 4 or less and the electrolyte substantially does not contain EC, DMC, or DEC, the DCR change rate is further reduced.

[0154] Industrial Applicability

[0155] The electrochemical device disclosed herein is suitable for use in vehicles, for example.

[0156] The present invention has been described in terms of the presently preferred embodiments, but this disclosure should not be construed as limiting. Various modifications and changes will undoubtedly become apparent to those skilled in the art of the art to which the present invention pertains by reading the above disclosure. Therefore, the appended claims should be interpreted as including all modifications and changes that do not depart from the true spirit and scope of the present invention.

[0157] Explanation of symbols

[0158] 1: porous carbon material, 2: pores, 3: inner wall of pores, 4: acidic functional groups, 5: electrolyte, 6: solvent, 7: anion, 10: positive electrode, 11x: exposed part of positive electrode core material, 13: positive electrode collector plate, 15: tab lead, 20: negative electrode, 21x: exposed part of negative electrode core material, 23: negative electrode collector plate, 30: separator, 100: electrode body, 200: electrochemical device, 210: battery case, 220: sealing plate, 221: gasket

Claims

1. An electrochemical device comprising: A positive electrode comprising a positive electrode active material reversibly doped with anions, A negative electrode including a negative electrode active material reversibly doped with lithium ions, and an electrolyte comprising a solvent and a lithium salt, The lithium salt comprises an imide lithium salt, The positive electrode active material comprises a porous carbon material, The total surface functional group amount per unit mass of the porous carbon material F (meq / g) and the area S (nm) of a circle with the average pore size of the porous carbon material as its diameter 2 ) satisfies the relationship 0.01≤F / S≤0.

2.

2. The electrochemical device according to claim 1, wherein: The imide-based lithium salt includes lithium bis(fluorosulfonyl)imide.

3. The electrochemical device according to claim 1, wherein The solvent includes a cyclic carbonate and a chain carbonate.

4. The electrochemical device according to claim 3, wherein: The volume ratio of the cyclic carbonate to the linear carbonate is 1 / 4 or more and 4 or less.

5. The electrochemical device according to claim 3, wherein: The cyclic carbonate contains propylene carbonate and substantially does not contain ethylene carbonate.

6. The electrochemical device according to claim 3, wherein: The linear carbonate contains ethyl methyl carbonate and substantially contains no dimethyl carbonate or diethyl carbonate.

7. The electrochemical device according to claim 1, wherein: The negative electrode active material includes hardly graphitizable carbon.

Citation Information

Patent Citations

  • Lithium ion capacitor

    JP2017216310A